Intestinal helminth infections and associated risk factors among adults in the Lao People's Democratic Republic - Sengaloun Phonekeo; Sengchanh Kounnavong; Manithong Vonglokham; Latsamy Siengsounthone; Anousin Homsana; Sascha Gummin; Penelope Vounatsu; Prawat Nittiyanant; Suchin Worawichawong; Wichai Aekplakorn; Peter Odermatt; Somphou Sayasone (BMC, 2023)
Abstract Background Helminthiases are highly endemic in Southeast Asia, including the Lao People's Democratic Republic (Lao PDR). This study aimed to assess the current intestinal helminth infections and the associated risk factors among adults across the Lao PDR. Methods A cross-sectional survey was conducted in 165 villages across 17 provinces and the Vientiane Capital, Lao PDR. A multi-stage sampling method was employed to select the adult study participants (≥ 18 years). Data collection included (1) interview of the study participants, (2) physical measurements, and (3) a five gram of stool sample from each study participant was collected and preserved in 10% formalin solution for intestinal helminth detection using formalin-ether concentration technique (FECT). Descriptive analysis was used to describe the socio-demographic characteristics of study participants and the prevalence of intestinal helminth infections. Logistic regressions were applied to test the association between intestinal helminth infection and individual risk factors. A P-value below 0.05 was considered statistically significant. Results A total of 2800 study participants were enrolled. Their average age was 46.0 years; 57.8% were female. Overall, 30.9%, 8.6% and 1.5% of study participants were infected with one, two, or three different intestinal helminth species, respectively. Among the study participants 21.6% were infected with hookworm, 18.8% with Opisthorchis viverrini-like (Ov-like) infection, 4.8% with Strongyloides stercoralis, 2.3% with Ascaris lumbricoides, 1.5% with Trichuris trichiura, and 3.3% with Taenia spp. Ov-like infection was of high prevalence in the southern (28.8%) and central (21.3%) provinces, while hookworm (26.3%), A. lumbricoides (7.3%), T. trichiura (3.1%), and Taenia spp. (4.2%) were prevalent in the northern provinces. Risk analysis showed that men were more likely to be infected with hookworm [adjusted odds ratio (aOR) = 1.2, P = 0.019]. The Lao-Tai ethnic group had a 5.2-times (P < 0.001) higher chance of having Ov-like infection than the minorities. Possession of toilet facility at home was associated with reduced odds for Ov-like (aOR = 0.4, P < 0.001) and hookworm (aOR = 0.6, P < 0.001) infections. Conclusions Our study provides a nationwide update of the intestinal helminth prevalence among adults in Lao PDR. To the best of our knowledge, this is the first Lao nationwide survey on intestinal helminth infections and risk factors in adults. It provides crucial information for national control programs for intestinal helminth infections in Lao PDR. Graphical abstract